2016
DOI: 10.1111/jace.14617
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the cold sintering process study for the densification and grain growth of ZnO ceramics

Abstract: With the cold sintering process (CSP), it was found that adding acetic acid to an aqueous solution dramatically changed both the densities and the grain microstructures of the ZnO ceramics. Bulk densities >90% theoretical were realized below 100°C, and the average conductivity of CSP samples at around 300°C was similar to samples conventionally sintered at 1400°C. Frequently, ZnO is also used as a model ceramic system for fundamental studies for sintering. By the same procedure as the grain growth of the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
154
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 214 publications
(172 citation statements)
references
References 43 publications
9
154
0
9
Order By: Relevance
“…First, solubility of ZnO is enhanced in acidic pH conditions, so solution-precipitation stage can start at lower temperatures. This is easily observed for the onset temperature for densification (Figure 2), as well as already observed in ZnO by CSP [20]. Furthermore, the incorporation of zinc acetate promotes larger dissolution of Zn 2+ and O 2-ions into the water boundary layer, as well as more Zn 2+ ions by the dissolution of the zinc acetate.…”
Section: Analysis Of the Defect Formation By Kelvin Probe Force Micromentioning
confidence: 65%
See 4 more Smart Citations
“…First, solubility of ZnO is enhanced in acidic pH conditions, so solution-precipitation stage can start at lower temperatures. This is easily observed for the onset temperature for densification (Figure 2), as well as already observed in ZnO by CSP [20]. Furthermore, the incorporation of zinc acetate promotes larger dissolution of Zn 2+ and O 2-ions into the water boundary layer, as well as more Zn 2+ ions by the dissolution of the zinc acetate.…”
Section: Analysis Of the Defect Formation By Kelvin Probe Force Micromentioning
confidence: 65%
“…However, Funahashi et al [20] reported recently a much lower activated energy of grain growth -43 kJ/mol -of ZnO under CSP, indicating a genuine sintering process at these low temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations